Bosnia and Herzegovina : Financial Sector Assessment Program. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses key findings and recommendations of the assessment on the Insurance Sector for Bosnia and Herzegovina (BiH). It is observed that 10 insurance companies, accounting for 40 percent of the nonlife market, have low solvency margins and may require supervisory action in the near future. Motor Third Party Liability insurance remains under pressure as market participants are not always compliant with the statutory tariff. It is expected that the Insurance Agency of Bosnia and Herzegovina will enhance the harmonization of entity-level regulations within BiH as well as with the European Union insurance directives.